Pelatihan Pemanfaatan Platform Facebook Sebagai Media Promosi pada Kelompok Tani Lele Sumber Jaya Tambun Selatan - Suhardoyo Suhardoyo; A Sudrajat; Roydawaty Bunga Sihol; Stanley Stanley (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Social media has become a very effective and efficient tool to promote products and services, including in the agricultural sector. The training was held at the Sumber Jaya Catfish Farmers Group Perum Griya Asri I Tambun Selatan District, Bekasi Regency and aimed to improve the ability of its members to utilize the Facebook platform as an effective and efficient promotional media. The methods used in this training include presentations, direct practice, and group discussions. Training materials include making accounts and Facebook pages, promotional content strategies, as well as interaction management techniques with customers. The results of this training showed an increase in the knowledge and skills of participants in using Facebook to promote catfish production in the Sumber Jaya catfish farmer group. Participants are expected to be able to create and manage Facebook pages, as well as design interesting content to increase visibility and sales. This training is expected to be a model for other farmer groups in utilizing social media to expand the market and improve the welfare of group members. The activities of implementing community service with the target of the purpose of the Community Service (PKM) implementing team to make field observations are to directly observe the location of the target area. The outputs to be achieved are: Publications in Print or Electronic Scientific Journal Articles in accredited national journals, articles in national journals are not accredited and local, articles in print or electronic media, both national and local, implementation documentation with photos of activities, and improvement the knowledge and skills of participants in using Facebook to promote catfish production in the Sumber Jaya catfish farmer group.